Terms of gendered representation: reassessing the role of elite women in early‒mid 18th dynasty funerary iconography from Thebes and El-Kab - Ellen Jones (2020)
Past studies on iconographic funerary material from ancient Egypt have traditionally focused on the male tomb owner, leaving his female relatives primarily characterised through their sexuality and how this benefited the tomb owner’s rebirth. This thesis reassesses this androcentric perspective, exploring whether there is a representational decorum in how female relatives are portrayed in a corpus of two early‒mid 18th Dynasty family clusters of monuments from Thebes and El-Kab, and their associated artefacts (see Chapter 2). A female relative is defined in Chapter 1 based on the presence of the core kinship terms—mwt ‘mother’, Hmt ‘wife’, snt ‘sister’ or ‘wife’, and sAt ‘daughter’—in a female figure’s caption. The discussion encompasses both a terminological analysis according to kinship term in Chapter 3 and an individual analysis focusing on the women and monuments in each family cluster in Chapter 4. Are there set ways in which women with these different kinship terms are depicted and could this infer a hierarchy between these terminological groups? What can these iconographic hierarchies potentially articulate about idealised female familial power relationships? How did the representation of a single woman change according to monument or according to kinship term? Which women are shown multiple times across their families’ monuments and artefacts, and why? Are kinship terms fully representative of the depiction of kinship within funerary iconography? The presence of such decorums suggests that female relatives were portrayed as a vital aspect of the tomb owner’s social network and self-presentation alongside his male relatives and colleagues. In this way, traditional approaches to ancient Egyptian funerary contexts are problematised in Chapter 5, drawing on anthropological theories from Feminist and Gender Anthropology and performance theory, in order to suggest a more nuanced, multifaceted, and gender balanced interpretation of the role of elite women in ancient Egyptian funerary monuments.